Investigating L2 learners' oral production and perception of a cycle of tasks with digital storytelling: an exploratory study in technology-mediated TBLT - Trevisol, Juliane Regina (2019)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão, Programa de Pós-Graduação em Inglês: Estudos Linguísticos e Literários, Florianópolis, 2019.